2019
DOI: 10.5194/isprs-annals-iv-4-w8-35-2019
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Bim–gis Conversion

Abstract: <p><strong>Abstract.</strong> Much work has been done on quality of geoinformation and interoperability between BIM and GIS. However, the intersection of the two – quality control of the conversion between BIM and GIS – remains uncharted. This discussion paper, based on empirical results, is one of the first steps towards mapping out a framework on errors and quality control in the context of BIM–GIS interoperability. In our work we focus on the conversion from IFC to CityGML, identifying sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…The "GeoBIM Benchmark 2019" (Noardo et al 2020) initiative commenced in 2017 and concluded in 2019, approaches BIM-GIS integration from two perspectives: (i) technical challenges in data interoperability and (ii) understanding requirements and use cases between the BIM and GEO domains (Ellul et al, 2020). Biljecki and Tauscher (2019) summarise in detail the most common errors noted in the IFC-CityGML conversion, focusing particularly on geometry, semantics and topology.…”
Section: Integration Challengesmentioning
confidence: 99%
See 2 more Smart Citations
“…The "GeoBIM Benchmark 2019" (Noardo et al 2020) initiative commenced in 2017 and concluded in 2019, approaches BIM-GIS integration from two perspectives: (i) technical challenges in data interoperability and (ii) understanding requirements and use cases between the BIM and GEO domains (Ellul et al, 2020). Biljecki and Tauscher (2019) summarise in detail the most common errors noted in the IFC-CityGML conversion, focusing particularly on geometry, semantics and topology.…”
Section: Integration Challengesmentioning
confidence: 99%
“…With regards to geometry, the major challenges involve the conversion of curved surfaces, missing geometric features and poorly geolocated geometries due to the use of local coordinate systems (Biljecki and Tauscher, 2019;Noardo et al, 2019). The "GeoBIM benchmark 2019" (Noardo et al, 2019) investigates the conversion from IFC to 3DGIS, using a variety of 3D models (Noardo et al, 2019) which represent different types of buildings.…”
Section: Integration Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, as mentioned before, by Arroyo Ohori et al [7], a thorough methodology converting both semantics and geometry consistently with the 3D city model features, as useful for the use of the model for analysis, had little success in previous efforts. In addition, it is quite common to find issues in the resulting data quality, consisting of semantics and geometric inaccuracies, inconsistency or loss of information, use of the wrong spatio-semantic paradigm in the resulting models, besides possibly more serious errors of invalidity, misplacement or deformations [33].…”
Section: Conversionsmentioning
confidence: 99%
“…In this case, the semantic mapping follows an approach that kept more semantics: the converted elements are buildingConstructiveElements, organized in bldg:Storeys and in one bldg:Building in turn, according to CityGML version 3 data model. The data model proposed by CityGML v.3 allows the validity of such kind of model, although it could be discussed that the spatio-semantic paradigm [33] is not changed in a harmonization effort with a GIS-consistent representation.…”
Section: Uptownifc Conversion To Citygmlmentioning
confidence: 99%